Dividend Policy as Moderating the Effect of Capital Structure, Profitability and Leverage on Firm Value - Anjani, Anggi Sukma; Badjuri, Achmad (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to determine the effect of capital structure, profitability and leverage on company value using dividend policy as a moderation for manufacturing companies on the Indonesia Stock Exchange in 2018-2021. This research method uses quantitative methods. The results of this study show that capital structure and leverage have a positive and significant effect on firm value while profitability has a negative and insignificant effect on firm value. Dividend policy can moderate the capital structure and profitability positively and significantly to firm value but moderate the influence of leverage negatively and not significantly to firm value.